A scandalous scot ebook - Ranney, Karen (2012)
"Karen Ranney writes with power, passion, and dramatic flair." —Stephanie Laurens "Ranney is a rich, rare find!" —Judith Ivory A Scandalous Scot is a scandalously entertaining tale of love and passion in the Scottish highlands from the queen of the Scottish historical romance novel, Karen Ranney. New York Times bestseller Ranney tells the tantalizing story of a handsome, haunted Scotsman returning in disgrace to his castle in Scotland after scandal ruined his reputation...only to court further damage to his name by falling in love with his maid, a feisty and outspoken beauty who hides some very shocking secrets of her own. Fans of Karen Hawkins and other bestselling historical romance writers who make the breathtaking highlands their preferred milieu will be swept away by this Scandalous Scot and his romantic trials, tribulations, and triumphs.